2010
DOI: 10.1016/s0034-7094(10)70057-x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study among Three Techniques of General Anesthesia for Ultrasound-Guided Transrectal Prostate Biopsy

Abstract: Sedation with propofol alone for biopsy is associated with greater postoperative pain and discomfort than in prostatic plexus block or systemic fentanyl. Besides hypnosis, intraoperative analgesia is required to guarantee postoperative comfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…However, we considered deep sedation to be superior because conscious sedation (without analgesia) can result in procedure interruption. Unfortunately, many studies have not reported the total dose of propofol used, whether it was delivered by bolus or continuous infusion, the duration of anesthesia, or the quality of sedation [7,17,18]. In a pilot study, we found that deep sedation could be induced in most patients with a bolus injection of i.v.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…However, we considered deep sedation to be superior because conscious sedation (without analgesia) can result in procedure interruption. Unfortunately, many studies have not reported the total dose of propofol used, whether it was delivered by bolus or continuous infusion, the duration of anesthesia, or the quality of sedation [7,17,18]. In a pilot study, we found that deep sedation could be induced in most patients with a bolus injection of i.v.…”
Section: Discussionmentioning
confidence: 89%
“…There are two main factors that contribute to pain during a TRUS-PBx are as follows: anal discomfort caused by ultrasound probe insertion, and penetration of the prostatic capsule by the biopsy needle [2]. Although propofol sedation has advantages over a PPNB, it is unable to completely prevent intraprocedural patient movement and postprocedural pain due to lack of analgesic effect [7]. Furthermore, pain during a TRUS-PBx was proven to be gradually accumulated from the first core biopsy to the last, even under anesthesia [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of this necessary but painful procedure, it is important to make use of analgesia or anesthe-sia to reduce the discomfort and thereby increase the number of samples taken and the success of the procedure. (12) For Family and Determination, this moment was marked by the search for definition of the disease and diagnosis:…”
Section: ] (Strength 76 Years)mentioning
confidence: 99%